Analyzing the professional practice context using three lenses: An essential step for responding strategically. Issue 2 (3rd April 2019) - Freeman, Andrew; Jauvin, Nathalie
Abstract: In the face of increased external controls on their practice and increased accountability obligations, health professionals such as occupational therapists must be able to act strategically with other stakeholders to reach consensus about service quality and the accompanying level of professional autonomy. Such strategic action requires certain competencies, including that of analyzing the context in which one's practice take place. In this article, we argue that the following three approaches, or lenses, should be used in this analysis: (1) accountability, (2) ethics, and (3) professional-as-worker . Individually, each lens offers a useful perspective, however, using all three permits a comprehensive and conceptually clear analysis. We present both the distinctive characteristics and complementary elements of the three lenses.